The Comparison of Dynamic and Static Footprint Parameters in Overweight Children - amirhosien Barati; Reza Azimi; Hosien Nabavi nik; Mihsen Ali Darchini Maragheh (Sport Sciences and Health Research)
Foot structure like other features of human body is various among different age groups and any changes in foot structure influence the function of other joint. Hence, many researchers are trying to prove the relationship between foot role and its pathology. The present study tried to compare footprint parameters (footprint angle, Staheli’s index, Chippaux – Smirak index and arch index) in the static and dynamic positions in overweight children. In this quasi-experimental study, 12 male overweight children (age range 10-12) were randomly selected. To measure the footprint parameters in two positions of static and dynamic, an ink - paper system was used. Then, ImageJ software was used to measure footprint angle, Staheli’s index, Chippaux – Smirak index and arch index. Mean and standard deviation were used to describe the data and the independent t test was used to compare the parameters. The findings showed no significant difference among angular parameters (P>0.05), but a significant difference in linear parameter between the static and dynamic positions (P